Combined genetic and transcriptomic analysis reveals three major signalling pathways activated by Myc‐LCOs in Medicago truncatula. Issue 1 (28th April 2015) - Camps, Céline; Jardinaud, Marie‐Françoise; Rengel, David; Carrère, Sébastien; Hervé, Christine; Debellé, Frédéric; Gamas, Pascal; Bensmihen, Sandra; Gough, Clare
Summary: Myc‐LCOs are newly identified symbiotic signals produced by arbuscular mycorrhizal (AM) fungi. Like rhizobial Nod factors, they are lipo‐chitooligosaccharides that activate the common symbiotic signalling pathway (CSSP) in plants. To increase our limited understanding of the roles of Myc‐LCOs we aimed to analyse Myc‐LCO‐induced transcriptional changes and their genetic control. Whole genome RNA sequencing (RNA‐seq) was performed on roots of Medicago truncatula wild‐type plants, and dmi3 and nsp1 symbiotic mutants affected in nodulation and mycorrhizal signalling. Plants were treated separately with the two major types of Myc‐LCOs, sulphated and nonsulphated. Generalized linear model analysis identified 2201 differentially expressed genes and classified them according to genotype and/or treatment effects. Three genetic pathways for Myc‐LCO‐regulation of transcriptomic reprogramming were highlighted: DMI3 ‐ and NSP1 ‐dependent; DMI3 ‐dependent and NSP1 ‐independent; and DMI3 ‐ and NSP1 ‐independent. Comprehensive analysis revealed overlaps with previous AM studies, and highlighted certain functions, especially signalling components and transcription factors. These data provide new insights into mycorrhizal signalling mechanisms, supporting a role for NSP1, and specialisation for NSP1 ‐dependent and ‐independent pathways downstream of DMI3 . Our data also indicate significant Myc‐LCO‐activated signalling upstream of DMI3 and/or parallel to the CSSP and some constitutive activity of the CSSP.